2013
DOI: 10.1007/s00792-013-0565-1
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and thermodynamic characteristics of thermo-alkali-stable xylanase from a novel polyextremophilic Bacillus halodurans TSEV1

Abstract: The purified extracellular xylanase of polyextremophilic Bacillus halodurans TSEV1 has been visualized as a single band on SDS-PAGE and eluted as single peak by gel filtration, with a molecular mass of 40 kDa. The peptide finger print and cloned xylanase gene sequence analyses indicate that this enzyme belongs to GH family 10. The active site carboxyl residues are mainly involved in catalysis, while tryptophan residues are involved in substrate binding. The enzyme is optimally active at 80 °C and pH 9.0, and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 37 publications
4
36
1
1
Order By: Relevance
“…The divalent transition metals such as Pb 2+ , Hg 2+ and Cu 2+ are known to catalyze auto-oxidation of cysteine that leads to the formation of intramolecular and intermolecular disulfide bridges or to the formation of sulfenic acid [39]; this could be the probable reason for enzyme inhibition by these metal ions. The inhibition and stimulation of the enzyme activity are similar to the native xylanase and other bacterial xylanases [24,38]. The inhibition of activity in the presence of N-bromosuccinimide suggests the presence of tryptophan residues in their active/substrate binding site, a characteristic property which is conserved in microbial xylanases and other enzymes [40].…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The divalent transition metals such as Pb 2+ , Hg 2+ and Cu 2+ are known to catalyze auto-oxidation of cysteine that leads to the formation of intramolecular and intermolecular disulfide bridges or to the formation of sulfenic acid [39]; this could be the probable reason for enzyme inhibition by these metal ions. The inhibition and stimulation of the enzyme activity are similar to the native xylanase and other bacterial xylanases [24,38]. The inhibition of activity in the presence of N-bromosuccinimide suggests the presence of tryptophan residues in their active/substrate binding site, a characteristic property which is conserved in microbial xylanases and other enzymes [40].…”
Section: Discussionmentioning
confidence: 85%
“…stable for 24 h in 8 M urea and 6 M guanidine-HCl. The enzymes from extremophilic microbes are known to display resistance to these chemicals [24,37]. The metal ions play an important role in catalysis as acceptors or donors of electrons and coordinating group between enzyme and substrate, or they may simply stabilize a catalytically active conformation of the enzyme [38].…”
Section: Discussionmentioning
confidence: 99%
“…Ba-Gt-amy inhibited activity in presence of Woodward’s reagent suggested that catalytic role of aspartic and glutamic acid residues. Woodward’s reagent K is a negatively charged reagent that covalently and irreversibly modifies carboxyl-containing amino acid residues (Adsul et al, 2009; Kumar and Satyanarayana, 2013). Strong inhibitory effect of NBS indicated structural and catalytic role of tryptophan residues in Ba-Gt-amy (Sharma and Satyanarayana, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Other xylanases such as Syncephalastrum racemosum Cohn. (58.0 kDa) [10] and Trichoderma reesei (90.0 kDa) [11] are also homodimers, whereas the majorities are identified as monomeric proteins in solution, for instance, Glaciecola mesophila KMM 241 (43.0 kDa) [12], Cohnella laeviribosi HY-21 (42.0 kDa) [13], B.halodurans TSEV1 (40.0 kDa) [14], and Remersonia thermophila CBS 540.69 (42.0 kDa) [15].…”
Section: Resultsmentioning
confidence: 99%